Mass of the Vermiform Appendix in Bangladeshi People - Rahman, M Mahbubur; Khalil, Mohsin; Khalil, Mansur; Jahan, Mst Khurshida; Shafiquazzaman, M; Parvin, Bilkis (Journal of Bangladesh Society of Physiologist, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This study was done to measure the weight of vermiform appendix in Bangladeshi people to augment the data regarding variational anatomy in our setting. A total 100 vermiform appendix (male - 60, female - 40) were excised from cadaver of different age and sex during routine post mortem examination in the autopsy laboratory of Forensic Medicine Department of Mymensingh Medical College. This cross-sectional study was done by convenient sampling technique. The weight depended on length and thickness. The weight decreases gradually with advancing age probably decreasing number of lymphatic follicle and that replaced by connective tissue. Lymphatic follicles were examined and estimated by microscope. For convenience of differentiating the weight of vermiform appendix in relation to age and sex, specimens were categorized in four age groups (up to 20 year, 21 - 35 years, 36 - 55 years, 56 - 70 years). Mean weight of vermiform appendix was maximum in group - B (4.07 ± SE 0.82 gm) and minimum in group D (3.01 ± SE 0.74 gm). The weight range was from 2 gm (group - D) to 5.50 gm (group - B). Diameter of lymphatic follicle was largest 43.08 micrometer in group-A, and least diameter was 3.08 micrometer in group - D. The range of number of lymphatic follicle was 1 to 6. Mean number of lymphatic follicle in male was 4.48 & in female were 5.40. Key Words: Human Vermiform, Appendix, Weight, Lymphatic, Follicle doi: 10.3329/jbsp.v3i0.1787 J Bangladesh Soc Physiol.2008 Dec;(3):8-12.